2018
DOI: 10.1093/jmcb/mjy039
|View full text |Cite
|
Sign up to set email alerts
|

Fenton reactions drive nucleotide and ATP syntheses in cancer

Abstract: We present a computational study of tissue transcriptomic data of 14 cancer types to address: what may drive cancer cell division? Our analyses point to that persistent disruption of the intracellular pH by Fenton reactions may be at the root of cancer development. Specifically, we have statistically demonstrated that Fenton reactions take place in cancer cytosol and mitochondria across all the 14 cancer types, based on cancer tissue gene-expression data integrated via the Michaelis–Menten equation. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 39 publications
4
66
0
Order By: Relevance
“…While these pathways can be activated by a wide range of conditions, one thing in common is: they can all be activated by intracellular stresses, particularly oxidative stress [20][21][22], and associated damages. Actually, all these pathways are strongly associated with responses to Fenton reactions as noted in our previous study [23]. Hence, we postulate that these pathways are transcriptionally regulated via DNA methylation in response to severe intracellular and micro-environmental oxidative stress.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…While these pathways can be activated by a wide range of conditions, one thing in common is: they can all be activated by intracellular stresses, particularly oxidative stress [20][21][22], and associated damages. Actually, all these pathways are strongly associated with responses to Fenton reactions as noted in our previous study [23]. Hence, we postulate that these pathways are transcriptionally regulated via DNA methylation in response to severe intracellular and micro-environmental oxidative stress.…”
Section: Resultssupporting
confidence: 68%
“…The intracellular and micro-environments of cancer cells may have specific stresses of the following types: persistent hypoxia, severe oxidative stress and stresses induced by rising intracellular pH [23,[29][30][31]. We have previously demonstrated that persistent hypoxia will lead to a persistent gap in ATP demand and supply [32].…”
Section: Resultsmentioning
confidence: 99%
“…It is, therefore, not surprising that iron accumulation is often observed in tumor tissues. Recently, iron accumulation at sites of chronic inflammation was proposed as a root cause of malignancy (1). Excess Fe 2+ and H 2 O 2 participate in Fenton reactions, generating reactive oxygen species (ROS), •OH and OH-.…”
Section: Introductionmentioning
confidence: 99%
“…Excess Fe 2+ and H 2 O 2 participate in Fenton reactions, generating reactive oxygen species (ROS), •OH and OH-. Glycolytic ATP generation and nucleotide synthesis are increased to neutralize excess OH − , which drives DNA synthesis and cell division (1). Furthermore, hydroxyl radicals can cause changes that lead to persistent inflammation and cell survival/proliferation signals (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation